The Food Groups of MyPyramid - Glenda L. Warren (EDIS, 2009)
FCS-8873, a 2-page illustrated fact sheet by Glenda L. Warren, lists each of the food groups, with descriptions and examples, and a key message for each group. Published by the UF Department of Family Youth and Community Sciences, December 2008. December 2019 reprint of 2008 content.